“LENDO MULHERES AFRO-BRASILEIRAS”: (RE) (DES) CONSTRUÇÃO IDENTITÁRIA E LETRAMENTO CRÍTICO EM UMA ESCOLA DE AUTORIA - NATHÁLIA DO NASCIMENTO GONÇALVES NOLASCO (2023)
“READING AFRO-BRAZILIAN WOMEN”: (RE)(DE)CONSTRUCTION IDENTITY AND CRITICAL LITERACY IN A SCHOOL PROGRAM FOR AUTHORSHIP This work aims to investigate the (re)(de)construction identity process of students in the first year of high school after the reading project called “Lendo Mulheres Afro-Brasileiras”, which contemplates the reading and discussion of texts focused on the identity of black women, in order to bring non-canonical black writers to the school context. To justify the research, the data collected takes into account the articulation through responses of a questionnaire produced on Google Forms, and the digital posters prepared by the students as a conclusion to the activities elaborate in a school program denominated “Escola da Autoria”. In the project, the classmates read texts written by Conceição Evaristo, Cristiane Sobral, Carolina Maria de Jesus, Meimei Basto and Jarid Arraes, as a premise for collective reflection about the theme. The choice of such writers is due to their cultural importance and because they bring, in their productions, the black women as a protagonist for their history. The theoretical basis of the work is based on studies on critical literacy (JORDÃO, 2016; FERREIRA, 2014 JESUS; CARBONIERI, 2016), in dialogue with studies about gender and identity, mainly focusing on representativeness of black women (HALL, 2005; MUNANGA, 2009; GOMES, 2002/2006; WERNECK, 2016, among others). The data analysis is developed through an interpretive methodology based on Applied Linguistics, the field in which the proposal is inserted (LOPES, 2020). As a result, we noticed that the students (re)signified questions about race in their readings and textual productions, as well as they built their impressions about black identity; however, they were did not able to manage the reconstruction of their identities — in which we believe is linked to the short time of the project development on Afro-Brazilian literature, mainly because the time was not enough to expand the discussion with them regarding their practices of reading and production. Thus, we stress the importance of educational practices that value Afro-Brazilian history and culture, which still need to be intensified in basic education teaching networks. Keywords: Identity. Afro-Brazilian Literature. Critical Literacy.